High-value utilization method of waste battery diaphragm
By mixing the waste battery separator with the papermaking black liquid for pre-treatment and catalytic pyrolysis, the problem of waste battery separator and papermaking black liquid is solved, efficient recycling and purification of resources is achieved, resource waste and environmental pollution problems are solved, and green Development requirements.
Patent Information
- Application Number
- CN202411542384.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art cannot effectively utilize waste battery separators and treat papermaking black liquid, resulting in waste of resources and environmental pollution.
By mixing the waste battery separator with papermaking black liquid for pretreatment, removing the alumina coating and performing catalytic pyrolysis, high-value aromatic hydrocarbons are prepared, and porous alumina and lignin are recovered at the same time, efficient utilization and purification of resources are achieved.
The high-value utilization of waste battery separators and papermaking black liquid has been achieved, the resource recovery rate and purification effect have been improved, the treatment cost has been reduced, and the requirements of green development have been met.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic waste utilization, and specifically relates to a method for high-value utilization of waste battery separators. Background Art
[0002] In recent years, the new energy vehicle industry has developed rapidly. Batteries are the core components of new energy vehicles, and their design life is generally 6 to 10 years. Currently, a large number of batteries are on the verge of retirement. Batteries are usually composed of positive electrodes, negative electrodes, electrolytes and separators. Among them, the separator, as an indispensable component of the battery, determines the number of cycles, cost and safety of the battery. The separator is mainly composed of polyethylene (PE) or polypropylene (PP), and an inorganic coating is used to improve the thermal stability of the separator and its affinity for the electrolyte. Commonly used inorganic coating materials include alumina, silica, etc. At present, alumina-coated separators have been commercialized in the field of new energy vehicles. It is estimated that by 2030, the cumulative amount of waste battery separators will reach 5 billion square meters. At present, the disposal methods of waste battery separators mainly include incineration and landfill. However, these technologies have disadvantages such as low efficiency and serious pollution. Therefore, it is urgent to find a green and efficient waste battery separator disposal technology.
[0003] Papermaking black liquor is a pollutant of the alkaline pulping and papermaking industry. Its main components are lignin and sodium hydroxide, and its pH value is 11 to 13. COD (chemical oxygen demand) in the wastewater discharged from the papermaking industry accounts for more than 40% of the total industrial COD discharge in the country, and the pollutants contained in papermaking black liquor account for more than 90% of the total discharge of the papermaking industry. In addition, it is difficult to treat and has serious harm to the environment. Therefore, the treatment of papermaking black liquor is the key to the treatment of wastewater in the papermaking industry.
[0004] Therefore, it is of great practical significance to develop a process that can not only efficiently treat waste battery separators but also purify papermaking black liquor. Summary of the invention
[0005] The present invention aims to solve the problems that existing methods for treating waste battery diaphragms cannot fully realize waste utilization, and that papermaking black liquor cannot fully realize purification and recycling. The present invention provides a new method for high-value utilization of waste battery diaphragms. The method can efficiently pretreat waste battery diaphragms and papermaking black liquor, and can realize the selective preparation of high-value aromatics by catalytic pyrolysis of waste battery diaphragms, recycle waste battery diaphragm coating materials, and purify papermaking black liquor. High-value utilization of waste battery diaphragms and purification of papermaking black liquor can be realized, thereby achieving green development.
[0006] In order to solve the above technical problems, the present invention provides a method for high-value utilization of waste battery separators, comprising the following steps:
[0007] S1, first mixing and filtering the waste battery separator and papermaking black liquor to obtain the first waste liquor and the pretreated battery separator with a portion of the aluminum oxide coating removed; wherein the pretreated battery separator is catalytically pyrolyzed to obtain aromatic hydrocarbons and solid carbon;
[0008] S2, coagulating and filtering the first waste liquid to obtain a second waste liquid and a first filter residue; wherein the first filter residue is first dried to obtain lignin;
[0009] S3, neutralizing, filtering and second drying the second waste liquid to obtain a second filter residue; and roasting the second filter residue and the solid carbon to obtain porous alumina.
[0010] In the present invention, the waste battery separator may be a waste lithium-ion battery separator, etc., and is mainly aimed at waste battery separators with aluminum oxide coatings.
[0011] According to some embodiments of the present invention, the papermaking black liquor is wastewater generated during the caustic soda pulping process. In the present invention, the papermaking black liquor is wastewater from the alkali pulping and papermaking industry, the main components of which are lignin and sodium hydroxide, and the pH value is 11-13.
[0012] According to some embodiments of the present invention, the solid-liquid ratio of the waste battery separator to the papermaking black liquor is 1: (100-200) g / mL. In the present invention, preferably, pre-treating the papermaking black liquor means immersing the waste battery separator in the papermaking black liquor at a solid-liquid ratio of (1:100) to (1:200) (g / mL), stirring at 60-90°C for 2-5h, then filtering, washing the filter residue with deionized water until neutral, and then drying.
[0013] According to some embodiments of the present invention, the first mixing conditions include: a temperature of 60 to 90° C. and a time of 2 to 5 hours.
[0014] According to some embodiments of the present invention, the weight of aluminum oxide in the pretreated battery separator is reduced by 10 to 40 wt% relative to the waste battery separator. In the present invention, partial removal of aluminum oxide coating refers to removing a portion of the aluminum oxide coating of the separator by pretreatment of papermaking black liquor, so that the aluminum oxide coating in the separator is reduced by 10 to 40 wt%.
[0015] According to some embodiments of the present invention, the catalyst for the catalytic pyrolysis is HZSM-5. Pyrolysis is a green and efficient thermal conversion technology, especially under the action of appropriate catalysts, it can quickly convert organic matter into fuels rich in specific high value-added compounds, such as aromatics. Aromatics are a class of hydrocarbons with a stable aromatic ring structure, which have special aroma and chemical properties and are widely used in the fields of chemical industry, medicine, etc. HZSM-5 has high catalytic performance in the preparation of aromatics by catalytic pyrolysis due to its strong acidity, high thermal stability and unique pore structure. HZSM-5 contains rich B acid sites and a unique MFI-type pore structure, which can effectively promote reactions such as cracking, hydrogen transfer, cyclization and aromatization of polymer pyrolysis volatiles, thereby promoting the formation of aromatics.
[0016] According to some embodiments of the present invention, the amount of catalyst used in the catalytic pyrolysis is catalyst:pretreated battery separator=(4-12):1.
[0017] According to some embodiments of the present invention, the conditions for the catalytic pyrolysis include: a temperature of 500 to 700° C. and a time of 10 to 20 min.
[0018] According to some embodiments of the present invention, after catalytic pyrolysis in S1, volatile components are obtained and condensed to obtain aromatic hydrocarbons. In the present invention, the condensation temperature is preferably 0-4°C.
[0019] According to some embodiments of the present invention, the coagulation method includes: performing a second mixing of the first waste liquid with one or more of chitosan, chitin and polyacrylamide.
[0020] According to some embodiments of the present invention, the liquid-to-solid ratio of the first waste liquid to one or more of chitosan, chitin and polyacrylamide is 1: (1-2) L / g.
[0021] According to some embodiments of the present invention, the second mixing conditions include: a temperature of 20 to 40° C. and a time of 10 to 30 min.
[0022] According to some embodiments of the present invention, the neutralization method comprises: introducing CO2 at a rate of 50 to 200 mL / min until the pH value of the solution reaches 6 to 8, and then filtering to obtain a second filter residue.
[0023] According to some embodiments of the present invention, the calcination conditions include: a temperature of 400 to 500° C. and a time of 1 to 2 hours.
[0024] According to some embodiments of the present invention, the conditions of the first drying and the second drying are independently selected from: temperature of 90-110°C and time of 12-24h. In the present invention, before the first drying and / or the second drying, preferably, distilled water is used for washing to neutrality.
[0025] According to some embodiments of the present invention, the waste battery separator is a battery separator having an aluminum oxide coating.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention can achieve high-value and clean utilization of waste battery diaphragms and papermaking black liquor: the organic components in the diaphragm are catalytically converted to produce high-value aromatics, which can be used as hydrogen storage liquid fuel or chemicals, while the inorganic components are recovered to form porous alumina; the papermaking black liquor can be used to recover lignin and achieve liquid purification.
[0028] (2) The present invention innovatively proposes a new method for selectively preparing aromatics by partially removing inorganic components of the diaphragm and strengthening catalytic pyrolysis. By partially removing the alumina coating of the diaphragm from papermaking black liquor, it can not only effectively reduce the heat and mass transfer resistance during the pyrolysis of the diaphragm and promote the pyrolysis and volatilization of organic components, but also strengthen the full contact between the volatile matter and alumina, exert the catalytic function of alumina, promote the decomposition of macromolecular substances into more small molecular olefins, and facilitate the subsequent cyclization, aromatization and other reactions under the action of the HZSM-5 catalyst, while increasing the yield of aromatics and reducing the coking and deactivation of the catalyst surface.
[0029] (3) The present invention proposes a new method for efficiently recovering lignin and purifying papermaking black liquor, thereby realizing the recovery of lignin and porous alumina. Papermaking black liquor contains a large amount of alkaline substances, which require a large amount of acidic reagents for neutralization during conventional disposal. The present invention uses them to react with inorganic components in the diaphragm, reducing the consumption of acidic reagents; at the same time, the filtrate after diaphragm pretreatment is rich in lignin, and chitosan coagulation can achieve efficient recovery of lignin and preliminary purification of black liquor. The dissolved alumina during diaphragm pretreatment will form aluminum hydroxide after CO2 is introduced. Aluminum hydroxide acts as a coagulant to gather the residual organic matter in the papermaking black liquor. After roasting, the volatilization of the organic matter will form high-quality porous alumina. In addition, the present invention uses CO2 to adjust the pH value of papermaking black liquor to 6-8, which meets the requirements of the national standard (GB3544-2008) and has the characteristics of being cheap and environmentally friendly. DETAILED DESCRIPTION
[0030] The present invention provides a method for high-value utilization of waste battery separators, and the present invention is further described below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0031] The calculation method of the liquid product yield in the following examples is as follows:
[0032] Liquid product yield = (mass of collected liquid product / mass of raw material) × 100%.
[0033] In the following examples, the content of aromatics in the liquid product was analyzed by gas chromatography / mass spectrometry and quantified by external standard method. The calculation method of the aromatics yield is as follows:
[0034] Yield of aromatic hydrocarbons = (mass of aromatic hydrocarbons / mass of raw materials) × 100%.
[0035] The percentages in the following examples are by mass unless otherwise specified.
[0036] Example 1
[0037] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:100 (g / mL), stir it at 60°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 80°C for 6h to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 10wt%.
[0038] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:1 (g / L), stirred at 20°C for 10 min, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 100°C for 18 h to obtain lignin.
[0039] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500℃ for 15min to obtain volatile components and solid carbon. The volatile components are condensed at 4℃ to obtain liquid products with a yield of 46.23%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 44.14%.
[0040] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 50mL / min until the pH of the filtrate is 6, then filter, wash the filter residue with deionized water until it is neutral, and then dry it at 120℃ for 6h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) are calcined at 400℃ for 1h to obtain porous alumina. It was determined that the average particle size of porous alumina is 60nm and the specific surface area is 258m 2 / g, pore volume is 0.467cm 3 / g.
[0041] Example 2
[0042] Take an appropriate amount of waste battery separators and immerse them in papermaking black liquor at a solid-liquid ratio of 1:200 (g / mL), stir at 60°C for 3 hours, filter, wash the filter residue with deionized water until it is neutral, and then dry at 120°C for 9 hours to obtain the pretreated waste battery separators with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 13wt%.
[0043] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 40°C for 10 min, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 99°C for 15 h to obtain lignin.
[0044] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 6:1, and quickly pyrolyze them at 500°C for 20 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 4°C to obtain a liquid product with a yield of 51.25%. The content of aromatics therein is analyzed by gas chromatography, and the yield of aromatics is calculated to be 47.42%.
[0045] Take an appropriate amount of the second waste liquid after chitin treatment, pass CO2 at a flow rate of 200mL / min until the filtrate pH = 7, then filter, and wash the filter residue with deionized water until neutral, and then dry it at 110℃ for 6h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 400℃ for 2h to obtain porous alumina. It was determined that the average particle size of porous alumina was 55nm and the specific surface area was 263m 2 / g, pore volume is 0.546cm 3 / g.
[0046] Example 3
[0047] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:150 (g / mL), stir it at 90°C for 3h, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 120°C for 21h to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 38wt%.
[0048] Polyacrylamide was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 40°C for 30 minutes, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 109°C for 15 hours to obtain lignin.
[0049] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 12:1, and quickly pyrolyze them at 600℃ for 15min to obtain volatile components and solid carbon. The volatile components are condensed at 3℃ to obtain liquid products with a yield of 63.68%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 57.45%.
[0050] Take an appropriate amount of the second waste liquid treated with polyacrylamide, pass CO2 at a flow rate of 100mL / min until the pH of the filtrate is 8, then filter, wash the filter residue with deionized water until it is neutral, and then dry it at 104℃ for 15h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) are calcined at 500℃ for 2h to obtain porous alumina. It was determined that the average particle size of porous alumina is 46nm and the specific surface area is 395m 2 / g, pore volume is 0.614cm 3 / g.
[0051] Example 4
[0052] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:110 (g / mL), stir it at 80°C for 5 hours, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 100°C for 12 hours to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 40wt%.
[0053] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 20°C for 20 minutes, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 110°C for 18 hours to obtain lignin.
[0054] Take an appropriate amount of the above pretreated waste battery separator and catalyst, mix them mechanically at the ratio of HZSM-5 / raw material = 9:1, and rapidly pyrolyze them at 600°C for 12 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 3°C to obtain a liquid product with a yield of 47.24%. The content of aromatics in the liquid product is analyzed by gas chromatography, and the yield of aromatics is calculated to be 44.84%.
[0055] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 150mL / min until the pH of the filtrate is 6, then filter, and wash the filter residue with deionized water until it is neutral, and then dry it at 99°C for 24h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) are calcined at 400°C for 1h to obtain porous alumina. It was determined that the average particle size of the porous alumina was 57nm and the specific surface area was 213m2 / g, pore volume is 0.309cm 3 / g.
[0056] Example 5
[0057] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:150 (g / mL), stir it at 60°C for 5 hours, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 99°C for 12 hours to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 29wt%.
[0058] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:1 (g / L), stirred at 30°C for 10 min, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 94°C for 13 h to obtain lignin.
[0059] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 11:1, and quickly pyrolyze them at 700℃ for 15min to obtain volatile components and solid carbon. The volatile components are condensed at 2℃ to obtain liquid products with a yield of 54.68%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 50.39%.
[0060] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 120mL / min until the filtrate pH = 7, then filter, and wash the filter residue with deionized water until neutral, and then dry it at 95℃ for 18h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 400℃ for 2h to obtain porous alumina. It was determined that the average particle size of porous alumina was 37nm and the specific surface area was 284m 2 / g, pore volume is 0.748cm 3 / g.
[0061] Example 6
[0062] Take an appropriate amount of waste battery separators and immerse them in papermaking black liquor at a solid-liquid ratio of 1:200 (g / mL), stir at 90°C for 2h, filter, wash the filter residue with deionized water until neutral, and then dry at 91°C for 14h to obtain the pretreated waste battery separators with the first waste liquid and part of the alumina coating removed. It was determined that the weight of the alumina coating in the separator after pretreatment decreased by 25wt%.
[0063] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 40°C for 30 minutes, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 98°C for 21 hours to obtain lignin.
[0064] Take an appropriate amount of the above pretreated waste battery separator and catalyst, mix them mechanically at the ratio of HZSM-5 / raw material = 12:1, and rapidly pyrolyze them at 600°C for 15 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 3°C to obtain a liquid product with a yield of 70.66%. The content of aromatics in the liquid product is analyzed by gas chromatography, and the yield of aromatics is calculated to be 66.22%.
[0065] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 190mL / min until the filtrate pH = 8, then filter, and wash the filter residue with deionized water until neutral, and then dry it at 96°C for 18h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 500°C for 2h to obtain porous alumina. It was determined that the average particle size of the porous alumina was 59nm and the specific surface area was 248m 2 / g, pore volume is 0.499cm 3 / g.
[0066] Example 7
[0067] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:160 (g / mL), stir it at 60°C for 3 hours, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 109°C for 24 hours to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 19wt%.
[0068] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:1 (g / L), stirred at 20°C for 10 min, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 99°C for 23 h to obtain lignin.
[0069] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 10:1, and quickly pyrolyze them at 700℃ for 12min to obtain volatile components and solid carbon. The volatile components are condensed at 2℃ to obtain liquid products with a yield of 55.21%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 51.66%.
[0070] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 160mL / min until the filtrate pH = 6, then filter, and wash the filter residue with deionized water until neutral, and then dry it at 94°C for 24h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 450°C for 1h to obtain porous alumina. It was determined that the average particle size of porous alumina was 51nm and the specific surface area was 221m 2 / g, pore volume is 0.421cm 3 / g.
[0071] Example 8
[0072] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:180 (g / mL), stir it at 80°C for 3h, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 95°C for 12h to obtain the pretreated waste battery separator with the first waste liquid and part of the alumina coating removed. It was determined that the weight of the alumina coating in the separator after pretreatment decreased by 32wt%.
[0073] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 20°C for 10 min, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 93°C for 16 h to obtain lignin.
[0074] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 12:1, and quickly pyrolyze them at 700℃ for 14min to obtain volatile components and solid carbon. The volatile components are condensed at 2℃ to obtain liquid products with a yield of 63.82%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 58.78%.
[0075] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 75mL / min until the filtrate pH = 7, then filter, and wash the filter residue with deionized water until neutral, then dry at 94°C for 18h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 420°C for 2h to obtain porous alumina. It was determined that the average particle size of the porous alumina was 55nm and the specific surface area was 425m 2 / g, pore volume is 0.424cm 3 / g.
[0076] Example 9
[0077] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:140 (g / mL), stir it at 70°C for 5 hours, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 109°C for 23 hours to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 36wt%.
[0078] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:1 (g / L), stirred at 30°C for 20 minutes, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 96°C for 15 hours to obtain lignin.
[0079] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them at the ratio of HZSM-5 / raw material = 8:1, and rapidly pyrolyze them at 650°C for 13 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 2°C to obtain a liquid product with a yield of 71.66%. The content of aromatics in the liquid product is analyzed by gas chromatography, and the yield of aromatics is calculated to be 69.82%.
[0080] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 50mL / min until the filtrate pH = 7, then filter, and wash the filter residue with deionized water until neutral, and then dry it at 93℃ for 23h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 490℃ for 1h to obtain porous alumina. It was determined that the average particle size of porous alumina was 64nm and the specific surface area was 563m 2 / g, pore volume is 0.636cm 3 / g.
[0081] Example 10
[0082] Take an appropriate amount of waste battery separator and immerse it in papermaking black liquor at a solid-liquid ratio of 1:190 (g / mL), stir it at 90°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 90°C for 24h to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 34wt%.
[0083] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:2 (g / L), stirred at 40°C for 30 minutes, and then filtered to obtain a second waste liquid and a first filter residue. The obtained first filter residue was washed with deionized water until neutral, and then dried at 110°C for 12 hours to obtain lignin.
[0084] Take an appropriate amount of the above pretreated waste battery separator and catalyst, mix them mechanically at the ratio of HZSM-5 / raw material = 7:1, and rapidly pyrolyze them at 700°C for 10 minutes to obtain volatile components and solid carbon. The volatile components are condensed at 0°C to obtain a liquid product with a yield of 66.23%. The content of aromatics in the liquid product is analyzed by gas chromatography, and the yield of aromatics is calculated to be 63.28%.
[0085] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 150mL / min until the filtrate pH = 8, then filter, and wash the filter residue with deionized water until neutral, then dry at 99°C for 12h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) were calcined at 450°C for 2h to obtain porous alumina. It was determined that the average particle size of the porous alumina was 57nm and the specific surface area was 257m 2 / g, pore volume is 0.485cm 3 / g.
[0086] Comparative Example 1
[0087] The method of Example 1 is different in that no papermaking black liquor is used, that is:
[0088] Take an appropriate amount of waste battery separator and catalyst and mix them mechanically according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500℃ for 15min to obtain volatile components and solid carbon. The volatile components are condensed at 4℃ to obtain liquid products with a yield of 22.68%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 20.31%.
[0089] Comparative Example 2
[0090] The method of Example 1 is followed, except that the papermaking black liquor is replaced with water, that is:
[0091] Take an appropriate amount of waste battery separator and immerse it in water at a solid-liquid ratio of 1:100 (g / mL), stir it at 60°C for 2h, then filter it, wash the filter residue with deionized water until it is neutral, and then dry it at 80°C for 6h to obtain the pretreated waste battery separator with the first waste liquid and part of the aluminum oxide coating removed. It was determined that the weight of the aluminum oxide coating in the separator after pretreatment decreased by 0.1wt%.
[0092] Chitosan was added to the first waste liquid at a solid-liquid ratio of 1:1 (g / L), stirred at 20° C. for 10 min, and then filtered to obtain a second waste liquid and a first filter residue.
[0093] Take an appropriate amount of the above pretreated waste battery separator and catalyst and mechanically mix them according to HZSM-5 / raw material = 4:1, and quickly pyrolyze them at 500℃ for 15min to obtain volatile components and solid carbon. The volatile components are condensed at 4℃ to obtain liquid products with a yield of 24.15%. The content of aromatics in them is analyzed by gas chromatography, and the yield of aromatics is calculated to be 22.93%.
[0094] Take an appropriate amount of the second waste liquid treated with chitosan, pass CO2 at a flow rate of 50mL / min until the pH of the filtrate is 6, then filter, wash the filter residue with deionized water until it is neutral, and then dry it at 110℃ for 24h to obtain the second filter residue. Finally, the second filter residue and solid char (pyrolysis solid product) are calcined at 400℃ for 1h to obtain alumina. The average particle size of alumina is 30nm and the specific surface area is 101m 2 / g, pore volume is 0.264cm 3 / g.
[0095] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for high-value utilization of waste battery separators, characterized in that: The following steps are involved: S1, first mixing and filtering the waste battery separator and papermaking black liquor to obtain the first waste liquor and the pretreated battery separator with a portion of the aluminum oxide coating removed; wherein the pretreated battery separator is catalytically pyrolyzed to obtain aromatic hydrocarbons and solid carbon; S2, coagulating and filtering the first waste liquid to obtain a second waste liquid and a first filter residue; wherein the first filter residue is first dried to obtain lignin; S3, neutralizing, filtering and second drying the second waste liquid to obtain a second filter residue; and roasting the second filter residue and the solid carbon to obtain porous alumina.
2. The method according to claim 1, characterized in that: The papermaking black liquor is wastewater generated during the pulping process using the caustic soda method.
3. The method according to claim 1 or 2, characterized in that: The solid-liquid ratio of waste battery separator to papermaking black liquor is 1:100-200 g / mL; and / or, The first mixing conditions include: temperature of 60 to 90° C. and time of 2 to 5 hours.
4. The method according to any one of claims 1 to 3, characterized in that The weight of aluminum oxide in the pretreated battery separator is reduced by 10 to 40 wt % relative to the waste battery separator.
5. The method according to any one of claims 1 to 4, characterized in that The catalyst for catalytic pyrolysis is HZSM-5; and / or, The amount of catalyst used in the catalytic pyrolysis is catalyst: pretreated battery separator = 4 to 12:1; and / or, The conditions for the catalytic pyrolysis include: a temperature of 500 to 700° C. and a time of 10 to 20 minutes.
6. The method according to any one of claims 1 to 5, characterized in that After catalytic pyrolysis in S1, volatile components are obtained and condensed to give aromatics.
7. The method according to any one of claims 1 to 6, characterized in that The coagulation method comprises: performing a second mixing of the first waste liquid with one or more of chitosan, chitin and polyacrylamide; Preferably, the liquid-to-solid ratio of the first waste liquid to one or more of chitosan, chitin and polyacrylamide is 1:1-2 L / g; Preferably, the second mixing conditions include: temperature of 20-40° C. and time of 10-30 min.
8. The method according to any one of claims 1 to 7, characterized in that The neutralization method comprises: introducing CO2 at a rate of 50 to 200 mL / min until the pH value of the solution reaches 6 to 8, and then filtering to obtain a second filter residue.
9. The method according to any one of claims 1 to 8, characterized in that The calcination conditions include: a temperature of 400 to 500° C.; a time of 1 to 2 hours; and / or, The conditions for the first drying and the second drying are independently selected from: a temperature of 80 to 120° C. and a time of 6 to 24 hours.
10. The method according to any one of claims 1 to 9, characterized in that The waste battery separator is a battery separator with an aluminum oxide coating.
Citation Information
Cited By
Method for converting waste battery diaphragm into high-value carbon material and application
CN120328530A
Method and use of spent battery separator conversion to high value carbon materials
CN120328530B